Does Exercise And Nutrition Style Affect Intestinal Micro-biota Diversity? - Genç, Ayça; Genç, Ayça (Mattioli 1885, 2020)
Aim: The aim of this study is to determine whether exercise and nutrition style has an effect on the intestinal microbiota diversity. Materials and Method: 15 healthy male volunteers between the ages of 18 and 24 participated in the study and they were grouped in three as professional athletes (n=5), amateur athletes (n=5) and sedentary individuals (n=5). Stool samples were taken from the participants once to find out their intestinal microbiota diversity, metagenomics analysis was conducted with New Generation Sequencing Method by using Illumina MiSeq analyzer and Nutrient Consumption questionnaire was given to find out their nutritional habits. Minitab 17 and SPSS 20.0 programs were used for the statistical analysis of the results and significance level was taken as p<0.0.5. Results: In our study which analyzed the species diversity, according to Shannon index, it was found that the group with the highest species diversity was the professional athletes group, while the group with the lowest species diversity was the sedentary individuals group. According to the Phylo diversity index, the group with the most phylo diversity was the professional athletes group, while the group with the least species diversity was the sedentary individuals group and a significant difference was found between amateur-professional, amateur-sedentary and professional-sedentary groups in terms of phylogenetic diversity (p<0.05). In addition, it was found that professional athletes had a diet consisting of protein predominantly, amateur athletes had a diet consisting of carbohydrates predominantly and sedentary individuals had a diet consisting of vegetable-fruit predominantly. Conclusion: it is thought that exercise influences intestinal microbiota diversity positively and different diets also have an influence in different microbial diversity between groups.
Keywords: Intestinal Microbiota; Diversity; Exercise; Nutrition